Sea level rise impact in residual circulation in Tagus estuary and Ria de Aveiro lagoon - Valentim, Juliana Marques (2018)
Nowadays, there is a special concern about the possible impact of sea level rise in hydrodynamic patterns of coastal systems and its consequence in contingent ecosystems. In the present work, the effects of sea level rise in residual circulation are analyzed in two of the most important Portuguese coastal systems, Ria de Aveiro lagoon and Tagus estuary. The role of rivers inflow on residual circulation is also analyzed under different sea level scenarios. Several projections of river discharges were considered and two scenarios for sea level were adopted: actual and locally predicted sea level rise. The methodology followed comprises the exploitation of previously validated 2D hydrodynamic numerical models (MOHID) developed for both systems. Results indicate that rivers discharge effect cannot be unconsidered in the long term hydrodynamic analysis for both systems, once residual currents intensity could be at least 40% and even 100% higher in maximum inflow than in typical inflow and no discharges scenarios, respectively. In Tagus estuary, the upper bay is the most affected area in a sea level rise scenario, namely in the upper zone (with extensive intertidal areas) where differences in the residual currents intensity can be higher than 100%. In Ria de Aveiro lagoon, differences between actual and sea level rise could be higher than 80%. Narrow and shallow channels are the most affected areas, revealing the significant impact of sea level rise in the intertidal zones. Consequently, the predicted changes in these systems hydrodynamics could influence the long term transport and their actual equilibrium and, as such, affect the natural state of the contingent biological communities.